Perception Abilities of L1 Cypriot Greek Listeners - Types of Errors Involving Plosive Consonants in L2 English - Kkese, Elena; Petinou, Kakia (My University, 2017)
This paper investigates the difficulties adult second language (L2) users of English encounter with plosive consonants in the L2. It presents the results of a task examining the acquisition of plosive voicing contrasts by college students with Cypriot Greek (CG) linguistic background. The task focused on the types of errors involving plosive consonants indicating that performance was significantly better in the voiceless plosive category. Participants were able to perceive voiced plosives but they treated such instances as a /nasal + voiced plosive/ sequence. Therefore, the question raised concerns different phonological contrasts realised through similar phonetic cues. The patterns observed suggested that this gap between phonetic cues and phonological contrast might explain why CG users have difficulties perceiving voiced English plosives. In this context, voice onset time (VOT) differences between the L1 and L2 are of crucial importance. In English, voiced plosives are characterised by short lag VOT while their voiceless counterparts fall within the long lag VOT continuum. The same phonetic contrast is used in CG to differentiate between single and geminate voiceless plosives. The results are discussed in relation to the frameworks of second language phonology and speech perception suggesting that the difficulties faced by the L2 listeners support the operation of a phonetic-phonological challenge. © 2016 Springer Science+Business Media New York
Keywords: Plosives; Prenasalisation; Second language phonology; Speech perception; VOT